Case report: Dandy-Walker malformation with occipital encephalocele and superadded meningitis - Saher Bano; Muhammad Aqib Faizan; Tooba Rehman; Jasleen Kaur; Jeevanjyot Singh (Heliyon)
Dandy-Walker malformation is a relatively uncommon abnormality known as cerebellar dysgenesis. This condition is characterized by cerebellar vermis hypoplasia, an upwardly rotated and malrotated vermis, an enlarged fourth ventricle, and an enlarged posterior fossa. This syndrome is thought to affect roughly one in every 35000 live births. Here we present a case of a preterm male of 33 + 4 weeks period of gestation who presented to us with a posterior midline cystic swelling at the occipital neck region. While there was no bruit in the transillumination of the cyst, there was a bruit in the transillumination of the skull.Due to his grunting respiratory rate of 44 breaths per minute and heart rate of 140 breaths per minute at presentation, he was admitted to the newborn critical care unit. The occipital cyst was excised following neurosurgery on board after getting a CT scan brain done which showed dilated ventricles with normal pressure hydrocephalus, cystic cerebellar changes, communicating with 4th ventricle and occipital encephalocele. Brain parenchymal changes were also noted and a CSF R/E was sent which showed meningitis and the patient was put on IV antibiotics empirically along with fluid supplementation. Objective: This case report aims to highlight the clinical presentation, diagnostic approach, and management of Dandy-Walker Malformation (DWM) in a preterm neonate, emphasizing the importance of early recognition and intervention in similar cases. Rationale: This case underscores the need for careful evaluation of neonatal cystic lesions, particularly in preterm infants, where timely diagnosis and appropriate management can significantly affect outcomes. By documenting this case, we aim to contribute to the understanding of Dandy-Walker Malformation and improve clinical practices in neonatal care.